Surface heterostructuring of laser-clad 316L stainless steel through texture-driven deformation twinning. (December 2022) - Kim, Rae Eon; Moon, Jongun; Kim, Eun Seong; Lee, Jungwan; Kim, Hyoung Seop
Abstract: Heterostructured materials produced by surface modification have attracted considerable attention owing to their exceptional mechanical properties. Laser-cladding is one of the promising processes to achieve heterostructures by creating a sandwich structure through a simple process. Herein, we propose a new strategy for designing heterostructured laser-clad materials containing dynamically reinforceable heterogeneity introduced through texture-engineering. The specific processing parameters for laser-cladding of 316L stainless steel were selected to induce a predominant crystallographic orientation favorable for twinning. The textured laser-clad alloy showed different textures between the coating and substrate regions, which exhibited a preferential orientation of <111> and <100>, respectively, along the loading direction. Plastic incompatibility was intensified due to the heterogeneous structure caused by the high dislocation density and localized deformation twinning in the coating region. Consequently, the present laser-clad alloys exhibited superior strength-ductility synergy compared to the other homogeneous materials, owing to the substantial hetero-deformation-induced hardening. Graphical abstract: Image, graphical abstract